2005
DOI: 10.1097/00000542-200504000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Reduces Intraoperative Blood Loss in Pediatric Patients Undergoing Scoliosis Surgery

Abstract: Intraoperative administration of tranexamic acid significantly reduces blood loss during spinal surgery in children with scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
204
5
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(225 citation statements)
references
References 22 publications
12
204
5
4
Order By: Relevance
“…The results of those few studies have been positive, but inconsistent. In a study of patients undergoing posterior spinal fusion for scoliosis, Sethna et al [27] revealed a 41 % decrease in intraoperative blood loss after the administration of TXA. No difference was found in the amount of blood transfused.…”
Section: Discussionmentioning
confidence: 99%
“…The results of those few studies have been positive, but inconsistent. In a study of patients undergoing posterior spinal fusion for scoliosis, Sethna et al [27] revealed a 41 % decrease in intraoperative blood loss after the administration of TXA. No difference was found in the amount of blood transfused.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, although PBL and TBL were significantly reduced in the tranexamic acid group, IBL was comparable between the two groups. Previous studies reported lower IBL in tranexamic acid-infused patients [18][19][20]. Tranexamic acid was infused following an initial pre-operative loading dose in the other studies, while we gave 10 mg.kg À1 of tranexamic acid with HES administration during the main surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed the safety of TXA use in scoliosis surgery upon postoperative examination detecting no clinical evidence of deep venous thrombosis 17 . Subsequent to these two studies, numerous other studies support its perioperative safety as shown in the studies included in our meta-analysis (Table 6).…”
Section: Discussion:-mentioning
confidence: 99%